2019
DOI: 10.1038/s41598-019-50840-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional redundancy of HSPA1, HSPA2 and other HSPA proteins in non-small cell lung carcinoma (NSCLC); an implication for NSCLC treatment

Abstract: Heat shock proteins (HSPs) are a large group of chaperones considered critical for maintaining cellular proteostasis. Their aberrant expression in tumors can modulate the course of processes defined as hallmarks of cancer. Previously, we showed that both stress-inducible HSPA1 and testis-enriched HSPA2, highly homologous members of the HSPA (HSP70) family, are often overexpressed in non-small cell lung carcinoma (NSCLC). HSPA1 is among the best characterized cancer-related chaperones, while the significance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 61 publications
6
43
1
Order By: Relevance
“…We found that a high reduction of HSPA2 levels in modified cells had no impact on proliferation ( Figure S2b ) and colony-forming ability ( Figure S2c ). Altogether, these results were in line with our earlier observations that shRNA-mediated knockdown of HSPA2 expression did not affect the proliferation, metabolic activity, and clone-forming ability of two cell lines originating from NSCLC, namely NCI-H23 (adenocarcinoma, arising from bronchial mucosal gland) and NCI-H1299 (derived from the metastatic tumor) [ 18 ].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…We found that a high reduction of HSPA2 levels in modified cells had no impact on proliferation ( Figure S2b ) and colony-forming ability ( Figure S2c ). Altogether, these results were in line with our earlier observations that shRNA-mediated knockdown of HSPA2 expression did not affect the proliferation, metabolic activity, and clone-forming ability of two cell lines originating from NSCLC, namely NCI-H23 (adenocarcinoma, arising from bronchial mucosal gland) and NCI-H1299 (derived from the metastatic tumor) [ 18 ].…”
Section: Resultssupporting
confidence: 89%
“…In order to exclude the possibility that even a small amount of HSPA2 remaining after gene knockdown may be sufficient to support cell growth, we used the CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats and CRISPR-associated protein 9) gene editing method. We generated HSPA2 knockout in the NCI-H1299 cell line, which we had used previously in HSPA2 knockdown study [ 18 ]. We established a knockout pool: a mixed population of edited CRISPR-A2 cells that contained around a 90% decreased level of HSPA2 ( Figure 1 b), as well as a control CRISPR-ctr pool.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their high conservation both in evolution and within the Hsp70 family, (human) Hsp70 proteins are often regarded as largely interchangeable (12)(13)(14)(15)(16)(17). However, specificity between Hsp70 machines does exist and different effects of the various Hsp70s have been reported (6,8,(18)(19)(20).…”
mentioning
confidence: 99%